2009
DOI: 10.1186/1472-6963-9-242
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of care for children with complex chronic health conditions: parents' perspectives

Abstract: BackgroundContinuity of care has been explored largely from academic and service provider perspectives, and in relation to adult patient/client groups. We interviewed parents of children with complex chronic health conditions to examine how their experiences and perceptions of continuity of care fit with these perspectives; and to identify the salient factors in the experience of, and factors contributing to, continuity in this population.MethodsParents of 47 elementary school-aged children with spina bifida, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
104
0
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(141 citation statements)
references
References 30 publications
18
104
0
19
Order By: Relevance
“…7 Alternatively, such parents may be able to make better use of what is offered, for example, by following recommendations for out-patient follow-up care more closely. 29 It is also possible that their children are healthier at the outset, or that they are more likely to avoid later health problems that are unrelated to the malignancy but that weaken the survival prospects. Given the widely accepted idea that the health care system should reach well out to everyone and the suspicion that this perhaps is not quite the case after all, a careful analysis of possible treatment differentials using longitudinal directly measured treatment data should be welcome in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…7 Alternatively, such parents may be able to make better use of what is offered, for example, by following recommendations for out-patient follow-up care more closely. 29 It is also possible that their children are healthier at the outset, or that they are more likely to avoid later health problems that are unrelated to the malignancy but that weaken the survival prospects. Given the widely accepted idea that the health care system should reach well out to everyone and the suspicion that this perhaps is not quite the case after all, a careful analysis of possible treatment differentials using longitudinal directly measured treatment data should be welcome in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Mothers developed the necessary expertise to meet their child's needs and if necessary challenging health professionals' decisions. Gibsons ' (1999) seminal work linked the notion of expert mother to the process of empowerment and the concept of critical reflection, and has informed the ongoing debate on parental expertise in the parent-health care professional partnership (for example Dickinson, et al, 2006;Miller, et al 2009;Nightingale, Sinha & Swallow, 2014). Understanding the nature of expert parents in terms of the attributes that constitute becoming an expert, and the ways health professionals engage with and incorporate expert parents' opinions into care decisions when working with children with long-term conditions, may facilitate better parent-professional engagement and collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the nature of expert parents in terms of the attributes that constitute becoming an expert, and the ways health professionals engage with and incorporate expert parents' opinions into care decisions when working with children with long-term conditions, may facilitate better parent-professional engagement and collaboration. Evidence suggests the quality of parent-professional relationships is variable and the process of developing effective relationships with health professionals can be stressful for parents (Dickinson et al 2006;Miller, Condin, McKellin, Shaw, Klassen & Sheps, 2009;Nuutila & Salanterä, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…First, we reviewed the literature about measures of continuity of care [9] and found that no measures for continuity of care specific for children. Thus, we chose to refer to Haggerty's generic measure of continuity of care and Miller's study [10,15,16] to generate item statements about continuity of care for children from parents' perspective. Second, we adapted 36 items from Haggerty's generic measure about care received by adult patients to parents' perspective on their child's care and to the Italian health care organisational context.…”
Section: Instrument Developmentmentioning
confidence: 99%
“…To assess continuity of care for these children, the critical role of parents, mediating between the child's needs and health care services and professionals, must be taken into account [10]. Parents should be involved in the assessment in order to measure and improve continuity of care for their children.…”
Section: Introductionmentioning
confidence: 99%